Neoliberal public policies and invisibilization of the quality of the curriculum in chilean higher education - González Ramírez , Isabel Ximena; Vargas Ugalde, Johanna Carla (Revista Pedagogía Universitaria y Didáctica del Derecho, 2022)
This article deals with public curricular policies in Chile over the last 50 years, for which it was investigated from a qualitative, exploratory-descriptive, critical and socio-historical perspective in the legal texts or reports on educational policies published during: the government of the Unidad Popular (1970-1973); the dictatorship (1973-1990); and the democratic period (1990-2020). This made it possible to identify and describe the neoliberal ideological elements that underpin current education policy, revealing both the transitions of power and the structures and modes of operation. It is concluded that the hegemonic mental models are entrenched in these policies, especially in the last two periods, with the current curriculum being a misaligned element of the relevant social problems and whose strategies and discursive structures have supranational hegemonic ideologies, therefore, their adherence or rejection does not slow down the advance of these macro-trends.